An optimized approach for automatic material distribution operations of bulldozers. (26th March 2018) - Hirayama, Masami; Whitty, Mark; Katupitiya, Jayantha; Guivant, Jose
Komatsu Ltd. is reinforcing the research and development of automation technology for our bulldozers. Based on this trend, a methodology for optimized distribution of materials is proposed and developed for dumping area operations using bulldozers in this article. The aim of this work is to develop a robust methodology to contribute to the development of an autonomous system as possible so that it can be applied to our commercial machines immediately. The identified problem is that no formulation has yet been produced which can be applied to achieve such objectives. To develop the methodology, firstly, problem formulation of a specific scenario at the dumping area is presented. Secondly, integer linear programming is applied to solve the distribution problem. A hybrid method combining heuristics techniques and local branching is utilized to make this methodology capable of providing fast and reasonable solutions. Lastly, simulation results with specific different distribution requirements are presented to show that the developed methodology can derive optimized solutions for different requirements with a stable computational performance.